(Innovating a new paradigm for international communication and opening a new chapter in strengthening cultural confidence: Internationalization and the mission of Chinese Journal of Integrative Nursing) - Ma Jenny (MaJenny) (中西医结合护理)
(Chinese Journal of Integrative Nursing (CJIN) is dedicated to promoting the internationalization of Chinese science and technology journals through innovative practices. Its pioneering technology of Authorship Metadata in Chinese, preserves authors' names in their native languages within global academic databases, demonstrating cultural confidence and enabling accurate tracking of academic achievements. By constructing an open science system, upgrading its technical platform, and ensuring the sustainable dissemination of resources, CJIN is committed to establishing an international academic hub in the field of integrative nursing. It aims to build bridges for cultural exchange, and transmitting the accumulated wisdom of Traditional Chinese Medicine nursing. )